Complete resection for a giant recurrent biliary cystadenoma: A surgical case report and review of literature. (June 2022) - Nguyen, Hoang; Nguyen, Ngoc Cuong; Thieu, Thi Tra My; Luong, Tuan Hiep; Tran, Ngoc Minh; Nguyen, Dang Hung; Nguyen, An Khang
Abstract: Background: Biliary cystadenoma is a rare cystic neoplasm of the liver. The clinical signs and symptoms are nonspecific, and treatment strategy is variable. Case presentation: In this study, we presented a case of a 32-year-old female with multilocular biliary cystadenoma. The patient underwent partial removal of the hepatic cyst two times in two different hospitals for two years and that the histopathological results were biliary cystic adenoma but was successfully treated by radical resection after the second recurrence. The patient underwent a J-shaped laparotomy. The giant cystic mass measuring 20 cm × 15 cm was below the position of the right anterior segment. This lesion pushed the liver parenchyma to both sides and compressed the hepatic hilum, causing dilatation of the intrahepatic bile ducts. The patient underwent complete resection of cystic mass. During the dissection, a 0.5mm-diameter fistula of left hepatic duct with the cyst was found. It was sutured using absorbable polydioxanone (PDS 6.0) and the cystic duct tube (C tube) (6 Fr) was inserted via the cystic duct into the left hepatic duct due to drain the bile fluid. Discussion: A biliary cystadenoma (BCA) primary origin is occasionally rare. Although imaging modalities such as ultrasound, computed tomography and magnetic resonance imaging could be suggestive, however, the definitive diagnosis is depended on the histological examination. Despite of being a benign tumor, it has a high risk of recurrence after conservative treatment. The potential risk for malignant is also present. Therefore, complete resection of the tumors is the treatment of choice. Conclusion: We herein present a report of a rare case with had a giant biliary cystadenoma (BCA) primary origin. This report aims to improve the understanding of the diagnosis and management of this uncommon disease. Highlights: A biliary cystadenoma (BCA) primary origin is occasionally rare, the clinical manifestations are variable and non-specific. BCA should be suspected when there is a multilocular and thick-walled cystic on liver imaging modalities. Histological examination and immunohistochemistry staining are considered as the gold standard. Radical surgery (enucleation or liver resection) must be still the most effective and major treatment approach.